THE OLD TOWN OF KUPANG: PERSISTENT ELEMENTS AND THE QUALITY OF THE SPACE BASED ON PUBLIC VIEWS - Dion B. Sarmento; Sunaryo, Rony Gunawan (International Journal on Livable Space, 2024)
Kupang's Old Town has undergone significant changes over time, influenced by foreign interventions that left behind a wide variety of historical stories and physical evidence as silent witnesses to the development of Kupang's Old Town. However, these historical elements are currently under threat due to a lack of protection and management.Aims: This research aims to study the physical changes in the urban network from the 17th century to the 21st century, highlighting elements that have disappeared, changed, or survived. The study also explores the community's perception of the surviving historical aspects.Methodology and Results: Using a descriptive qualitative approach, [1]the results show significant changes within the area, including the loss of certain elements, changes in function, and the continuation of others. The community values the aspects that have survived, especially the historical buildings, which are seen as an integral part to the area's identity. There is a desire to improve the quality of space in Kupang's Old Town today.Conclusion, Significance and Implication: The study recommends the development of policies that integrate urban growth, historic preservation, and stakeholder participation to achieve a balanced management of Kupang’s Old Town.